ICT TOOLS FOR CREATIVITY IN TEACHING LEARNING PROCESS - Dr. Pooja M. Pathak (EPRA International Journal of Multidisciplinary Research (IJMR), 2023)
ICT is a broad term stands for Information Communication Technology. ICT tools for teaching and learning cover everything from digital infrastructures such as printers, computers, laptops, tablets, etc., to software tools such as Google Meet, Google Spreadsheets, etc. In traditional classrooms, a teacher’s basic instructional tools for displaying information are chalkboards, multipurpose boards, bulletin boards and charts. But in today’s modern scenario, tools of many professions are changing at an incredible rate and that education is no exception. The impact of technology has led to the increased use of computers for presenting information in many of today’s classrooms. To make ICT teaching and learning more interactive, various platforms and tools have been created and updated over the period of time. Innovative ICT tools used in classroom teaching which helps teachers to integrate in their subject, for teaching-learning and assessment. There are numerous subject specific free of cost ICT tools available on online and offline platforms which can be used for teaching, learning and assessment. They are used by teachers to encourage participation and engage learning in their classrooms. ICT can also be used by teachers to promote collaborative work and creativity across a wide range of subjects. This study aims at highlighting the superiority of ICT tools for facilitating student learning, retention and attitudes.